Atividade antimicrobiana e composição química de méis do Estado da Bahia - Peralta, Edna Dória (2010)
Antimicrobial resistance has stimulated research with honey, effective in treating various human diseases. Nevertheless, studies on its biological properties in Brazil are scarce, and specially for honeys from Bahia until now no records were found. Then, in the present work the antimicrobial activity and chemical composition of honey from Bahia was evaluated. Chapter 1 of this study evaluates 37 samples of A. mellifera honey and 16 of stingless bees (T. angustula, M. scutellaris, M. quadrifasciata and Plebeia sp), collected in Bahia, from 2005 to 2008. Chapter 2 deals with the comparison between two periods of production of A. mellifera honey from the same hive. The antimicrobial activity of honey was determined by the agar diffusion and minimal inhibitory concentration. The samples were tested against E. coli, S. aureus, P. aeruginosa and C. albicans. Parameters such as pH, acidity, water activity (aw), color and phenolic compounds were analyzed. It was realized Spearman correlation analysis to verify the relation between the physicochemical parameters and antimicrobial activity. The phenolic profile was determined by high-performance liquid chromatography and the data was treated by multivariate analysis of principal coordinates. The results showed that honey bees from Bahia have antimicrobial activity and this activity could not be attributed to just one of the analyzed parameters.